A Review on Rasayana - Chulet, Rahul; Pradhan, Pankaj (Pharmacognosy Reviews)
Rasayana is one of the eight clinical specialities of classical Ayurveda. Rasayana replenish the vital fluids of our body, thus keeping us away from diseases. The rasayana therapy enhance the qualities of rasa, enriches it with nutrients so one can attains longevity, memory, intelligence, freedom from disorder, youthfulness, excellence of luster, complexion and voice, optimum development of physique and sense organs, mastery over phonetics and brilliance. Taking rasayana is helpful to increase the immunity of the person to keep him away from disease and also reverses the disease process and prevents the re-occurrence. The Rasayanas are rejuvenators, nutritional supplements and possess strong antioxidant activity. They also have antagonistic actions on the oxidative stressors, which give rise to the formation of different free radicals. Ocimum sanctum, Tinospora cordifolia, Emblica officinalis, Convolvulus pluricaulis, Centella asiatica, Bacopa monniera, Withania somnifera, Triphala rasayana, Chyawanprash, Brahma rasayana are very important rasayanas which are described in ayurveda and proved by new researches.
Keywords: Rasayana; Antioxidant activity; Bacopa monniera; Withania somnifera